(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
God is much more than a personality aspersonality is understood by the human mind; he is even far more than any possibleconcept of a super personality. But it is utterly futile to discuss suchincomprehensible concepts of divine personality with the minds of materialcreatures whose maximum concept of the reality of being consists in the ideaand ideal of personality. The material creature’s highest possible concept ofthe Universal Creator is embraced within the spiritual ideals of the exaltedidea of divine personality. Therefore, although you may know that God must bemuch more than the human conception of personality, you equally well know thatthe Universal Father cannot possibly be anything less than an eternal,infinite, true, good, and beautiful personality.